On the resistant pathogens problem of the recurrent vulvovaginal candidiasis - Yu V Dolgo-Saburova; A K Mirzabalaeva; N N Klimko (IP Berlin A.V., 2014)
The article presents the results of a prospective clinical study of susceptibility of recurrent vulvovaginal candidiasis (RVVC) to fluconazole in vitro. During the period from 2003 to 2013 1155 patients were examined. Major causative agent in 88% of cases is Candida albicans. The RVVK cause in 12% of patients were 11 species of C. not-albicans, which are dominated by Candida glabrata (3,6%), Candida krusei (2,0%) and Candida parapsilosis (1,8%). Fluconazole in vitro was susceptible to pathogens RVVK 94%. Among the isolates of C. albicans, susceptibility to fluconazole in vitro was 98,8%. Secretion frequency of C. not-albicans strains, sensitive to fluconazole was 53%.